Dinámica de los contaminantes atmosféricos emitidos por fuentes fijas del cantón Latacunga - Luna Villalobos, Diana Fernanda (2017)
In Ecuador the industries grow well and in the Latacunga canton is not the exception causing quantities of air pollution since there is not enough information of this kind of study. The objective of this research was to diagnose the current situation using feasible methodologies to determine the information of the soil, flora and fauna in the area of company influence CEDAL S.A in order to do a data base for the decision making on environmental policies. First, it was projected forty points, which were rejected taing into account a probability graph of wind direction, and in this form were settled down fifteen points of sampling since of stationary source to two kilometers around, where each point has a distance of 500 meters. Next, it was made the recognition of the researching area and some visits of the sample points (in-situ), where the use of the soil was registered, flora and current fauna. With the obtained data, it was made a database and a geo-referential map. The diagnostic results of the soil, flora and fauna into the influence area, where is located the stationary source, it shows a significant impact to the environment, 80% of soil is used for human settlements and 10 % by native species at this region. Regarding the fauna of this region it was determined that weren´t any mammal’s species of great importance. Birds represent 15% being able to adapt to anthropic means. In addition, Domestic animals such as cattle were also recorded occupying 0.5% in the sector, registering in the N.09C y N.15C. The elaboration of database and a geo referential map of the soil use, flora and fauna will help to Regulatory institutions to improve the quality of the environment and strengthen new environmental regulations or decisions to monitor, control, and mitigation of air quality in Latacunga canton